Ankylosis of permanent teeth: a case report and literature review - Jacobs Stanley G. (Sciendo, 1989)
A case report describing an ankylosed permanent maxillary canine which was brought into the arch by a combination of surgery and orthodontics is used as a basis to review the literature concerning many aspects of the management of ankylosed permanent teeth, The literature indicates surgical luxation is a two edged sword, that is, it may cause ankylosis if used with surgical exposures but it can also be the only means of treating ankylosis. The treatment of the canine which is the subject of this case report resulted in damage to the tooth. Vanarsdall's recent# contributions in this field are detailed.